(1096) The Role of the Price in the Plan of Development دور السعر في خطة التنمية - Werner Wunderlich. (2020)
This study explores the multifaceted role of pricing within the framework of economic development planning, emphasizing both theoretical foundations and practical applications. To provide context, it begins with an overview of the social and economic prerequisites for comprehensive planning, as well as the main goals and content of such efforts. The German Democratic Republic serves as a case study to illustrate these principles in practice. While the integration of material, value, and financial planning is widely recognized as essential, achieving this unity remains a significant challenge. Despite extensive research, many detailed aspects of this integration remain unresolved. This study addresses the core requirements and interdependencies of planning processes, offering preliminary insights into these complex relationships.